Bioethics and COVID-19: Considering the Social Determinants of Health - Valera, Luca; López Barreda, Rodrigo (Frontiers in Medicine, 2022)
In this paper we focus on a novel bioethical approach concerning the ethical implications of the Social Determinants of Health (SDs) in the time of COVID-19, offering a fresh interpretation of our agency and responsibility in the pandemic era. Our interpretation is grounded on the idea that our health basically depends on factors that go beyond our organism. We stress, thus, the radical importance of circumstances to ethically assess an action. Due to this centrality of the SDs in our bioethical assessments –that implies that our health does not exclusively depend on our choices, behaviors, and lifestyle– we affirm that we are not entirely responsible for our wellness or diseases. As health depends on economic, social, cultural, and environmental factors, we argue that the analysis of personal responsibility facing personal health status should receive further consideration. Indeed, we stress the importance of the concept of “shared responsibility” in collective decisions: if we make many decisions collectively, we are also collectively responsible of these decisions. Furthermore, to responsibly tackle the social inequalities that are the underlying cause of disparities in health outcomes, we propose two main strategies based on the Capability Approach: 1. empowering the individuals, especially the most vulnerable ones; and 2. designing preventive policies and interventions that provides an opportunity to address the disparities moving forward. This will help us going beyond the “individualistic medical ethics paradigm” and integrating our concept of health with social factors (e.g., the SDs), based on a more relational and interdependent anthropological thought.